Work Rewards and Teachers’ Professional Commitment in Indonesian Private Schools: The Mediating Role of Work Ethic - Anna Rufaidah; Sri Setyaningsih; Eka Suhardi (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2026)
This study examined the relationship among work rewards, work ethic, and teachers’ professional commitment among private junior high school teachers in East Bogor Regency, Indonesia. The study employed a quantitative cross-sectional survey design involving 178 teachers selected through multistage proportional random sampling from 23 private junior high schools. Data were collected using structured questionnaires measuring work rewards, work ethic, and teachers’ professional commitment. Data analysis was conducted using Partial Least Squares Structural Equation Modelling with SmartPLS 3 software. The findings demonstrated that work rewards positively and significantly influenced work ethic and teachers’ professional commitment. Work ethic also demonstrated a positive and significant relationship with teachers’ professional commitment. In addition, work ethic served as a significant partial mediator in the relationship between work rewards and teachers' professional commitment, indicating that work rewards enhanced teachers' professional commitment both directly and indirectly through work ethic. The coefficient of determination analysis demonstrated moderate explanatory power for the proposed structural model. The study contributes theoretically to educational management literature by strengthening empirical understanding regarding the relationship among organizational appreciation, professional behaviour, and teachers’ professional commitment within private educational institutions. Practically, the findings emphasize the importance of developing institutional strategies that combine organizational appreciation, professional support, and sustainable professional development to strengthen teachers’ professional commitment.